1996
DOI: 10.1007/bf02658504
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action on glucose transport and plasma membrane GLUT4 content in skeletal muscle from patients with NIDDM

Abstract: We investigated the response of the glucose transport system to insulin, in the presence of ambient glucose concentrations, in isolated skeletal muscle from seven patients with non-insulin-dependent diabetes mellitus (NIDDM) (age, 55 +/- 3 years, BMI 27.4 +/- 1.8 kg/m2) and seven healthy control subjects (age, 54 +/- 3 years, BMI 26.5 +/- 1.1 kg/m2). Insulin-mediated whole body glucose utilization was similar between the groups when studied in the presence of ambient glucose concentrations (approximately 10 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
252
0
9

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 359 publications
(280 citation statements)
references
References 50 publications
13
252
0
9
Order By: Relevance
“…Tissue-specific regulation of GLUT4 has also been described in animals fed a high fat diet, which resulted in decreased GLUT4 mRNA expression in white adipose tissue but not skeletal muscle [51,52]. Further analysis has suggested that the defect in muscle glucose uptake in patients with Type 2 diabetes could be associated with impairments in trafficking and/or translocation of GLUT4 to the plasma membrane [53,54,55]. In agreement, high fat-induced skeletal muscle insulin resistance in animals has been associated with defects in the translocation and intrinsic activity of GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specific regulation of GLUT4 has also been described in animals fed a high fat diet, which resulted in decreased GLUT4 mRNA expression in white adipose tissue but not skeletal muscle [51,52]. Further analysis has suggested that the defect in muscle glucose uptake in patients with Type 2 diabetes could be associated with impairments in trafficking and/or translocation of GLUT4 to the plasma membrane [53,54,55]. In agreement, high fat-induced skeletal muscle insulin resistance in animals has been associated with defects in the translocation and intrinsic activity of GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…Akt/protein kinase B is then phosphorylated through phosphorylation of the tyrosine site of IRS-1. In obese, insulin-resistant subjects, GLUT4 translocation to the plasma membrane is attenuated by the inhibition of insulin signaling pathways such as IR, IRS-1 and Akt activation (Zierath et al 1996). Therefore, to clarify the activation of GLUT4 translocation associated with improvement of insulin resistance by Fx, we investigated IR mRNA expression and Akt phosphorylation in the soleus and EDL muscles.…”
Section: Ir Mrna Expression and Akt Phosphorylation By Fx In Soleus Amentioning
confidence: 99%
“…Therefore, we determined the presence of the glucose transporter proteins GLUT1 and GLUT4 in the plasma membrane of rat skeletal muscle to assess whether in vivo glucose infusion induced the translocation of the transporters. Because insulin induces the translocation of GLUT4 particularly to the transversal tubules (TT) of the plasma membrane [42,50,51] this membrane compartment was also studied. The identity and purity of the TT fraction was assessed by the presence of a 1 dihydropyridine receptor which is exclusively located in the TT membranes [52].…”
Section: Insulin Signalling Cascadementioning
confidence: 99%